Do UK crops and grassland require greater inputs of sulphur fertilizer in response to recent and forecast reductions in sulphur emissions and deposition?. (16th February 2016) - Webb, J.; Jephcote, C.; Fraser, A.; Wiltshire, J.; Aston, S.; Rose, R.; Vincent, K.; Roth, B.
Abstract: UK emissions of sulphur dioxide decreased by 94% between 1970 and 2010 and are projected to decrease by another 50% by 2020 as coal fired power stations are decommissioned. We used the Community Multiscale Air Quality model to create maps of sulphur (S) deposition to assess the impact of these forecast decreases in S emissions on net S deposition to crops in England and Wales. Currently, average S deposition, net of S leaching, varies little between the UK regions, being greatest in Yorkshire and Humberside (Y&H), at ca. 5–6 kg/ha S, and least in Wales, at ca. 3–4 kg/ha S. However, even in Y&H S deposition is no more than 25% of S uptake by cereals and only ca. 10% of S uptake by oilseed rape (OSR). By 2020, net S deposition is predicted to decrease by between 30 and 60% and will be no more than 15% of S uptake by cereal crops and <10% of S uptake by OSR. We conclude that, with the exception of a few localities, net S deposition is currently making only a minor contribution to crop S requirements and this small contribution will continue to decline. We recommend S be applied at the rates currently advised, as either mineral fertilizer or livestock manures (or a combination of both), to all crops and grass grown on sandy soils or in areas of >375‐mm overwinter rainfall. The need for S fertilizer appears to be greatest for grass swards cut more than once.